Survey of LEU olympiad 2012 for young mathematicians - Jakaitytė, Eglė; Kaučikas, Algirdas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2012)
The texts and solutions of the LEU young mathematicians olympiad – 2012 are presented.
Keywords: mathematical olympiads; problem solving